PERSEPSI ORANG TUA SISWA DAN GURU TENTANG PENDIDIKAN DASAR GRATIS - Syamsu Alam Hamid (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2012)
This study aimed to determine 1 ) whether they ( parents and teachers ) have a clear understanding of the free education policy 2 ). How their perceptions about the meaning of " free " in the administration of education services as well as the role and responsibility of government stork , parents and other stakeholders in the implementation of free primary education policy . 3 ) How do they think about the model of implementation of free primary education policy , including the role of society in overseeing the program. (FGD - Focus Group Discussion ) is used as the primary method to achieve the objectives of this research . Parents of students and teachers realize that education is the main factor and the needs of future asset depan.Biaya important as education becomes a major factor when parents want to send their anaknya.Terutama of families of middle economic strata , feel experiencing difficulties with respect to the cost of education is getting more expensive . This is due in addition to the rising prices of basic needs is also the need for additional school expenses necessary to improve the quality of education of children, also there is still performed peraktek school tuition fees . In addition BOS considered not effective in helping parents to overcome the limitations of school needs